THE HIERARCHY OF NEEDS IN WEINER’S LITTLE EARTHQUAKES - Andi Inayah Soraya (Lensa Budaya: Jurnal Ilmiah Ilmu-Ilmu Budaya, 2018)
This research aimed to describe the Hierarchy of Needs manifested to the main character in the novel. It applies psychological Maslow’s theory, who proposes five steps of Hierarchy of Needs covering Psychological Needs, Safety Needs, Belongingness and Love Needs, Esteem Needs, and Self-Actualization. This research used descriptive qualitative method. The data in this research were in written form taken from the dialogue and narration of the novel. The result of analysis indicates that all of characters have a lot ofpower to fulfillthe Hierarchy of Needs.